POLITIK HUKUM KETENAGAKERJAAN DALAM REFORMASI REGULASI NASIONAL - Miftahul Huda Huda; Mulyanto Mulyanto (LPPM Universitas Putera Batam, 2026)
Employment regulatory reform in Indonesia is part of the dynamics of national legal politics aimed at adapting the legal system to the needs of economic development and investment. Regulatory changes, particularly through the omnibus law approach, have sparked debate regarding the balance between worker protection and labor market flexibility. This study aims to analyze the direction of labor law politics in national regulatory reform and its implications for the principle of protecting workers' rights within the framework of a state based on the rule of law. This study uses normative legal research methods with both legislative and conceptual approaches. The results indicate that labor regulatory reform tends to strengthen the orientation of economic growth through the simplification of norms and flexibility of employment relations, but has the potential to shift the principle of protection as a fundamental characteristic of labor law. The evolving legal politics demonstrate a tension between the welfare state paradigm and the free market paradigm. In conclusion, labor regulatory reform needs to be directed at a balance between legal certainty, social justice, and the protection of workers' constitutional rights. This study recommends the need to strengthen oversight mechanisms and public participation in the formation of labor policies to ensure legal reform remains in line with the principles of the rule of law and social justice.